Theoretical and organizational foundations of ordering and conducting a forensic audit examination - Глібко, В. М. (Theory and practice of jurisprudence, 2016)
The main tasks that are accomplished by a forensic audit examination are worded in the paper, issues related to ordering and conducting a forensic audit examination are considered. The analisys of the essential normative acts is provided.